Menelusuri Jejak Kisah Merbau Bersiram Darah: Kajian Khazanah Budaya Melayu Riau - Halimatu Sa’diah; Jarir Jarir (Universitas Palangka Raya, 2025)
Folklore is a cultural artifact that stores local wisdom and timeless character education value. One of the folk tales from the Malay coast of Bengkalis that is full of meaning is Merbau Bersiram Blood, a legend about betrayal, slander and a fight for honor between two royal commanders. Using a qualitative-descriptive approach, this article traces the story as a representation of moral education in the construction of Malay culture. Narrative analysis of story line, characters, and symbolism shows how values ​​such as honesty, loyalty, and the consequences of injustice are subtly but powerfully embedded in the structure of the story. This story not only tells of a bloody tragedy, but also reflects the social mechanisms of Malay society in responding to betrayal and cultivating ethics. By re-exploring this story, this article raises the urgency of revitalizing oral traditions as a contextual and meaningful character learning medium, especially in local culture-based education ecosystems. Blood-Drenched Merbau is not just a legend, but a moral voice that echoes from the past for the future generation of Malays.